Research and development excellence from Malaysian Universities : prosperity through global research & innovation - Mohd. Zulkifli Mohd. Ghazali, Tan Sri Prof. Ir. Dr., 1951-; Ariffin Samsuri; Public Universities Research and Development Exhibition (3rd : 2005 : Kuala Lumpur) (Skudai : Penerbit Universiti Teknologi Malaysia, 2005)
PSZJBL